2018
DOI: 10.1590/0074-02760170444
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterisation of Leptospira inadai serogroup Lyme isolated from captured rat in Brazil and comparative analysis with human reference strain

Abstract: Leptospira inadai is classified as a species of the Leptospira intermediate group that has been poorly studied due to its apparent insignificance to human and animal health. Nevertheless, over the last two decades the species has been described in human cases in India and in carrier animals in Ecuador. Here, we present the first identification and genomic characterisation of L. inadai serogroup Lyme isolated from captured rodent in Brazil. Even though the M34/99 strain was not pathogenic for hamsters, it was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Also, many recent studies revealed that species belonging to the intermediate clade may be associated with clinical disease in humans 13,14,18,26−28 . Despite these new ndings, little is known about the intermediate clade and its pathogenicity to animals and humans remains unclear, since it was not possible to reproduce the disease in a hamster model 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, many recent studies revealed that species belonging to the intermediate clade may be associated with clinical disease in humans 13,14,18,26−28 . Despite these new ndings, little is known about the intermediate clade and its pathogenicity to animals and humans remains unclear, since it was not possible to reproduce the disease in a hamster model 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, there are very few studies about these species and its detection has been reported only in the following countries: Perú, Ecuador, Colombia, Argentina, Venezuela and Brazil 13,15,19,21,27,29 . In Argentina, the only study available reports the detection of intermediate leptospiral DNA in human samples 28 , but there is no further research until the present day, mainly due to the lack of an accurate diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation